Non-parametric linearised data driven modelling and force tracking control of a magnetorheological damper - K., Hudha; H., Jamaluddin; P. M., Samin; R. A., Rahman (Inderscience Enterprises Limited, 2005)
This paper presents a Non-Parametric Linearised Data Driven (NPLDD) approach to model the dynamic performance of Magnetorheological (MR) damper. The proposed model is developed based on experimental data and consists of a pair of subsystems, namely, positive and negative relative acceleration of the damper. In each subsystem, the hard points of experimental data are mapped into look-up table for a set of applied voltage signals. The results of the study show that the proposed model is able to describe the behaviour of the damper adequately and the force tracking controller has the ability to track the desired force well.